2019
DOI: 10.5812/ijo.55047
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Clinical Periodontal Parameters After Orthodontic Appliance Removal: A Prospective Study

Abstract: Objectives: Considering the changes in periodontal parameters after orthodontic treatment and lack of adequate evidence on the return of these parameters to normal, the aim of this study was to evaluate the time needed for recovery of periodontal parameters to normal after debonding. Methods: In this prospective study, 24 patients (21 females and 3 males) with a mean age of 18.86 ± 4.64 years were included, who were in the final stage of their orthodontic treatment and ready for debonding of orthodontic bracke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(17 reference statements)
0
0
1
Order By: Relevance
“…The changes in BI were not significant among the groups. In contrast with the results of our study, Hadzic et al 27 and Soheilifar et al 28 reported that an increment in the mean value of the BI was observed at each check-up after the placement of a fixed orthodontic appliance. Evaluation of BI measurements among research groups using Pearson correlation coefficient, Spearman Rank Correlation and 2-tailed T -test revealed different results.…”
Section: Discussioncontrasting
confidence: 99%
“…The changes in BI were not significant among the groups. In contrast with the results of our study, Hadzic et al 27 and Soheilifar et al 28 reported that an increment in the mean value of the BI was observed at each check-up after the placement of a fixed orthodontic appliance. Evaluation of BI measurements among research groups using Pearson correlation coefficient, Spearman Rank Correlation and 2-tailed T -test revealed different results.…”
Section: Discussioncontrasting
confidence: 99%